Algae-Based Supplements Claiming Weight Loss Properties - Fernandes, Fátima (2024)
Funding Information: This work received financial support from Portuguese national funds (FCT/MCTES, Fundação para a Ciência e Tecnologia and Ministério da Ciência, Tecnologia e Ensino Superior) through the projects UIDP/5006/2020. F. Fernandes thanks FCT for funding through program DL 57/2016—Norma transitória (Ref. DL57/2016/CP1346/CT0018). Publisher Copyright: © 2024 by the authors.